Maxillary advancement using external distraction device internally: A case report and review of the literature - Esmaeelinejad, Mohammad; Khojasteh, Arash (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: Advancing the dysplastic maxilla in cleft palate patients is a challenging issue. This study aimed to report a case of maxillary advancement in a cleft palate patient by distraction osteogenesis technique. Materials and methods: A 21 year old woman with the chief complaint of retruded maxilla was planned to be treated by distraction method. An external craniofacial distraction device was used in a total different way to advance the hypoplastic maxilla. In the second section of the study a review table of advancing techniques in such cases was designed and presented. Results: The amount of maxillary advancement was 10 mm horizontally and 5 mm inferiorly. The distraction procedure gave the ability of moving the maxilla in two directions. The tooth show was improved and paranasal area and A point were advanced to help in gaining a straight profile. The remained discrepancy was corrected by mandibular setback procedure. Conclusions: Distraction osteogenesis may be a reliable treatment plan in advancing hypoplastic midface in cleft palate patients. The results of this method may be more sufficient than routine orthognathic surgery.